2016
DOI: 10.1556/036.103.2016.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function in young females of Kolkata, India – Revisited

Abstract: Rapid economic and industrial growths imposed significant impact on human health including the pulmonary health. Questions were raised regarding the validity of the existing prediction norms of pulmonary function tests (PFTs) in a particular population. The present study was conducted to investigate the applicability of the existing norms for PFTs in young healthy non-smoking female university students of Kolkata, India. Significant difference was noted in vital capacity (VC), forced vital capacity (FVC), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…It is important that the preceding inspiration is fast and any pause at full inspiration be minimal (i.e., only for 1 -2 seconds). The test assumes a full inhalation before beginning the forced exhalation, and it is imperative that the subject takes a complete inhalation before beginning the maneuver [7]. Table 1 shows the pulmonary function parameters investigated in this study with definition.…”
Section: Pulmonary Function Tests (Pfts)mentioning
confidence: 99%
See 3 more Smart Citations
“…It is important that the preceding inspiration is fast and any pause at full inspiration be minimal (i.e., only for 1 -2 seconds). The test assumes a full inhalation before beginning the forced exhalation, and it is imperative that the subject takes a complete inhalation before beginning the maneuver [7]. Table 1 shows the pulmonary function parameters investigated in this study with definition.…”
Section: Pulmonary Function Tests (Pfts)mentioning
confidence: 99%
“…(1) Table 1 The definitions of forced expiratory (FEV1), peak expiratory flow (PEF) and forced vital capacity (FVC) [7].…”
Section: Pulmonary Function Tests (Pfts)mentioning
confidence: 99%
See 2 more Smart Citations
“…In some previous studies the investigators have shown that different factors such as gender, race, ethnicity, weight, and height, affect the pulmonary function test. (21)(22)(23)(24)(25) In another study conducted in Iran, it was also mentioned that air-borne particles also affect the pulmonary function test. (26) some studies has also shown an association of decline in lung function among individuals exposed to occupational dust particles.…”
Section: Discussionmentioning
confidence: 99%